Croatian National Minorities in the Print Media - Mesić, Milan (2005)
In contrast to prevailing expectations, connected with the world-wide image of the South Eastern Europe and Croatia itself, this paper, based on content analysis of the leding daily nespaper in the country, does not prove that the print media are markedly negatively and derogatively oriented in their presentation of national minorities in Croatia.